Quality of Life among University Students in a Single Malaysian Institute - Ahmed Al-Naggar, Redhwan; T. Osman, Muhamed; Musa, Ramli (penseejournal.com, 2013)
Quality of life of university students in an important issue in order to tackle the physical, mental, social problems as early as possible to produce future leaders for the future developed nation. The aim of this study was to evaluate health-related quality of life (HRQoL) among university students in Malaysia and to identify factors that might be associated with their HRQoL. A cross-section study was conducted among 239 university students. QoL was measured according to WHOQoL- BREF questionnaire which was a short questionnaire consisting of 26 items (version of World Health Organization Quality of Life assessment; WHOQoL-100). Scoring was done according to the WHOQoL- BREF procedures manual. All scores of the domains ranged between 4 to 20. t-test and was used in univariate analysis and Multiple linear regression using backward analysis allowing to obtain the final model for each domain. The final model was chosen depending on R² and the p value of model. a p value less than 0.05 was considered significant. The majority of students were males, 22 years of age and older, single and from medical and health faculty (69.9%, 95.4%, 59.4%; respectively). Overall, the highest average scores of QoL was found in the environment domain (13.97) and the lowest was in physical health domain (13.14). For univariate analysis gender and family monthly income were significantly associated with social relationships (p=0.04, p=0.018; respectively). In other hand, gender and juniority were found to be significantly associated with the environment domain (p=0.034, p=0.012; respectively). In multivariate analysis, being younger than 22 years, senior and with high family monthly income had higher scores in social relationships among university students (p=0.037, p=0.038, p=0.009; respectively). In terms of environmental domain , being male, senior and single had higher scores compares to be female, junior and ever-married students (p=0.014, p=0.022, p=0.044; respectively). Our findings indicate that multiple factors are associated with students' QoL. Health education programs that would target modifiable risk factors may improve students' QoL.